To simplify the expression \( (9x^2 - 6x + 2) - (x^2 + 4x - 39) \), we will first distribute the negative sign across the second polynomial and then combine like terms.
-
Distribute the negative sign: \[ (9x^2 - 6x + 2) - (x^2 + 4x - 39) = 9x^2 - 6x + 2 - x^2 - 4x + 39 \]
-
Now, combine like terms:
- Combine the \(x^2\) terms: \(9x^2 - x^2 = 8x^2\)
- Combine the \(x\) terms: \(-6x - 4x = -10x\)
- Combine the constant terms: \(2 + 39 = 41\)
-
Putting it all together, we get: \[ 8x^2 - 10x + 41 \]
So, the simplified expression is: \[ \boxed{8x^2 - 10x + 41} \]